THE EFFECT OF MARKET ORIENTATION ON PERFORMANCE WITH ENVIRONMENTAL UNCERTAINTY AS A MODERATING VARIABLE - Syarifah Hudayah; Muhammad Ikbal (Universitas Hayam Wuruk Perbanas, 2013)
Market orientation of banks is related to business performance through the environmentaluncertainty as moderator. Environmental uncertainty is an important factor in both the marketingand management literature. In this case, it is important to see how an increase in environmentaluncertainty influences the market orientation – performance relationship. Data forthis study were collected using questionnaires mailed to the top executives throughout 132local development banks (BPD) in 30 state-regions (province) in Indonesia, representing allthe local development banks. The responses were obtained from 26 BPD as a response ratewith 96 respondents. First, result indicates market orientation has a strong effect on banksperformance through the degree of environmental uncertainty faced by the banks. Second,the relationship between market orientation and performance weakens much for banks inhigh uncertainty of the environments. Higher uncertainty of the environment can weaken therelationship between market orientations and business performance. Environmental uncertaintycomplicates the management in determining market orientation; the impact, businessperformance is unlikely to be achieved at the maximum conditions.